Cerebellopontine angle tumour in a case of metastatic carcinoma breast: a diagnostic dilemma - Kaur, Avneet; Kharkwal, Suman; Sarkar, Sushanta; Kalra, Pawan (International Surgery Journal, 2022)
Tumours of the cerebellopontine angle are mostly vestibular schwannomas with metastasis being a rare diagnosis. But, metastasis if present, are usually from a breast or a lung primary. We presented a case of a 67 year old postmenopausal lady with luminal. A carcinoma left breast who developed a recurrence on aromatase inhibitor with bone metastasis. She also presented with a cerebellopontine angle tumour which, because of its unusual presentation, presence of a recurrent breast disease with metastasis and mutation testing, raised the suspicion of a brain metastasis but was finally confirmed to be a vestibular schwannoma by histopathology.